Inbound marketing and its influence on customer acquisition with AI in self services - Hernández Zambrano, Paul Alfredo; Loor Moreira, Jacqueline Alexandra; Granda Garcia, Marco Iván (Ingeniería Solidaria, 2025)
Introduction: This article is the product of a master’s research project titled The Impact of Digital Marketing Technologies on the Competitive Strategies of Lodging SMEs in Manta, highlighting its relevance in an increasin-gly digitalized business environment. The study was conducted at the Universidad Laica Eloy Alfaro de Manabí in Manta in 2025. Problem: Despite the growing importance of digital marketing, many lodging SMEs face difficulties in imple-menting these tools due to a lack of knowledge and resources, which limits their competitiveness. Objective: The main objective is to determine how digital marketing and technology influence the competitive strategies of lodging SMEs, evaluating their effectiveness in customer loyalty and market differentiation. Methodology: An exploratory, descriptive, and correlational approach was used, applying surveys with a Likert scale to 70 lodging SMEs. The validity of the instrument was verified using Cronbach’s Alpha coefficient, yiel-ding a value of 0.960. Results: The findings indicate that digital marketing and technology show a positive correlation (0.844) with competitive strategies, highlighting the influence of social media and feedback on marketing differentiation and the breadth of products and services. Conclusion: The research concludes that the effective implementation of digital marketing strategies is crucial for improving the competitiveness of lodging SMEs, enabling stronger customer connections and increased loyalty. Originality: This study provides a unique perspective on the intersection between digital marketing and compe-titiveness in the accommodation sector, contributing to existing literature. Limitations: Limitations include the sample size and the lack of longitudinal analysis, suggesting the need for further research.